Antibiotic-induced black hairy tongue: two case reports and a review of the literature. Issue 10 (October 2020) - Ren, Jing; Zheng, Yao; Du, Hui; Wang, Shan; Liu, Linna; Duan, Wanshi; Zhang, Zeping; Heng, Lijun; Yang, Qi
Black hairy tongue (BHT) is characterized by a discolored, hairy tongue. We herein report two cases of BHT associated with antibacterial agents and review previous cases. In Case 1, a 17-year-old girl with a central neurocytoma was administered intravenous piperacillin–tazobactam for postoperative infection, and BHT developed 12 days later. Her symptoms resolved 8 days after she discontinued the piperacillin–tazobactam and brushed her tongue three times daily. In Case 2, a 65-year-old man was administered intravenous piperacillin–tazobactam and levofloxacin to treat multidrug-resistant Pseudomonas aeruginosa, and BHT developed 15 days later. The piperacillin–tazobactam was discontinued and the patient brushed his tongue, and the discoloration gradually subsided thereafter. However, the BHT reappeared after linezolid treatment. The patient had adverse drug reactions to both the piperacillin–tazobactam and linezolid treatments. The BHT might have been related to antibiotic use in both cases. We identified 19 cases of antibiotic-related BHT in a literature search, but none were related to piperacillin–tazobactam use. In all cases, symptoms resolved after discontinuation of the drug and brushing of the tongue. BHT may be a rare adverse effect of antibiotics. Treatment strategies include removal of the causative agents, mechanical debridement, and good oral hygiene.